Inflammatory Cytokines Presented from Polymer Matrices Differentially Generate and Activate DCs In Situ. (2nd August 2013) - Ali, Omar A.; Tayalia, Prakriti; Shvartsman, Dmitry; Lewin, Sarah; Mooney, David J.
Abstract During infection, inflammatory cytokines mobilize and activate dendritic cells (DCs), which are essential for efficacious T cell priming and immune responses that clear the infection. Here, macroporous poly(lactide‐co‐glycolide) (PLG) matrices are designed to release the inflammatory cytokines GM‐CSF, Flt3L, and CCL20 in order to mimic infection‐induced DC recruitment. The ability of these infection mimics to function as cancer vaccines is tested via induction of specific anti‐tumor T cell responses. All vaccine systems tested are able to confer specific anti‐tumor T cell responses and long‐term survival in a therapeutic B16‐F10 melanoma model. However, GM‐CSF and Flt3L vaccines result in similar survival rates and outperformed CCL20‐loaded scaffolds, even though they have differential effects on DC recruitment and generation. GM‐CSF signaling is identified as the most potent chemotactic factor for conventional DCs and significantly enhanced surface expression of MHC(II) and CD86(+), which are utilized for priming T cell immunity. In contrast, the use of Flt3L vaccines leads to greater numbers of plasmacytoid DCs, correlating with increased levels of T cell‐priming cytokines that amplify T cell responses. These results demonstrate that 3D polymer matrices modified to present inflammatory cytokines may be utilized to effectively mobilize and activate different DC subsets in vivo for immunotherapy.